Stimulated Biosynthesis of an C10-Deoxy Heptaene NPP B2 via Regulatory Genes Overexpression in Pseudonocardia autotrophica - Park, Heung-Soon; Kim, Hye-Jin; Han, Chi-Young; Nah, Hee-Ju; Choi, Si-Sun; Kim, Eung-Soo (Frontiers in Microbiology, 2020)
Polyene macrolides, such as nystatin A1, amphotericin B, and NPP A1, belong to a large family of valuable antifungal polyketide compounds that are typically produced by soil actinomycetes. Previously, NPP B1, a novel NPP A1 derivative harboring a heptaene core structure, was generated by introducing two amino acid substitutions in the putative NADPH-binding motif of the enoyl reductase domain in module 5 of the NPP A1 polyketide synthase in Pseudonocardia autotrophica. This derivative showed superior antifungal activity to NPP A1. In this study, another novel derivative called NPP B2 was developed, which lacks a hydroxyl group at the C10 position by site-specific gene disruption of the P450 hydroxylase NppL. To stimulate the extremely low expression of the NPP B2 biosynthetic pathway genes, the 32-kb NPP-specific regulatory gene cluster was overexpressed via site-specific chromosomal integration. The extra copy of the six NPP-specific regulatory genes led to a significant increase in the NPP B2 yield from 0.19 mg/L to 7.67 mg/L, which is the highest level of NPP B2 production ever achieved by the P. autotrophica strain. Subsequent in vitro antifungal activity and toxicity studies indicated that NPP B2 exhibited similar antifungal activity but significantly lower hemolytic toxicity than NPP B1. These results suggest that an NPP biosynthetic pathway refactoring and overexpression of its pathway-specific regulatory genes is an efficient approach to stimulating the production of an extremely low-level metabolite, such as NPP B2 in a pathway-engineered rare actinomycetes strain.